Order, Disorder, And Criticality : Advanced Problems Of Phase Transition Theory. - Holovatch, Yurij (World Scientific, 2004)
This book reviews some of the classic aspects in the theory of phasetransitions and critical phenomena, which has a longhistory. Recently, these aspects are attracting much attention due toessential new contributions. The topics presented in this bookinclude: mathematical theory of the Ising model; equilibrium andnon-equilibrium criticality of one-dimensional quantum spin chains;influence of structural disorder on the critical behaviour of thePotts model; criticality, fractality and multifractality of linkedpolymers; field-theoretical approaches in the superconducting phasetransitions.